STRATEGI KOMUNIKASI DIVISI PUBLIC RELATIONS PLN DISTRIBUSI JAWA BARAT DALAM SOSIALISASI SUBSIDI LISTRIK TEPAT SASARAN - Lyza Audina Pangesti (Jurusan Ilmu Komunikasi UTM, 2018)
ABSTRACTThis thesis discuss about the communication strategy which have been implemented by public relations of PLN due to socializing well-targeted electricity subsidy program in West Java. This Well-targeted electricity subsidy program is a government program which cuts the electricity subsidy for middle income homes 900—watt customer, where West Java province is ranked the highest in Indonesia. The goal of this research is to know the steps of communication strategy which have been implemented by public relations PLN West Java Distribution due to socializing well-targeted electricity subsidy program. This research uses constructivist paradigm, qualitative approach and case-study research strategy. The data were collected by in depth interview and documentation study. The result revealed that the public relations of PLN becomes one of the communicator who planned and give the instructions to public relations of PLN West Java Distribution in socializing well-targeted electricity subsidy program. The communication strategy steps which have been implemented by public relations of PLN due to socializing well-targeted electricity subsidy program are determined the communicator, recognizes the audiences, set the method and last selection and media uses.